Patient characteristics associated with the need for high doses of tenapanor hydrochloride in dialysis patients with hyperphosphatemia: A pooled analysis of three clinical trials - Nobuo Nagano; Shin Tokunaga; Shinji Asada; Masafumi Fukagawa; Tadao Akizawa (PLOS One, 2026)
Tenapanor hydrochloride (tenapanor), a selective inhibitor of the sodium/hydrogen exchanger isoform 3, is approved for management of hyperphosphatemia in patients undergoing dialysis. Dosage is initiated at 5 mg twice daily and can be titrated to 10, 20, or 30 mg twice daily according to clinical response and tolerability. However, patient characteristics associated with the need for higher tenapanor doses remain unclear. This study is a pooled analysis of data from three clinical trials conducted in Japan, in which tenapanor dose was titrated starting from 5 mg twice daily. After 8 weeks of treatment, dialysis patients were retrospectively categorized into a low-dose group (5 or 10 mg/dose; n = 127) and a high-dose group (20 or 30 mg/dose; n = 85) according to their final dose. Univariate and multivariate analyses were performed to identify baseline factors independently associated with higher tenapanor dose requirements. At Week 8, mean ± standard deviation tenapanor dose was 8.0 ± 2.5 mg twice daily in the low-dose group, and 26.7 ± 4.9 mg twice daily in the high-dose group. Serum phosphorus levels decreased gradually over 8 weeks in both groups; however, no significant between-group difference in change from baseline was observed. Baseline comparisons showed significant differences in serum phosphorus, serum tartrate-resistant acid phosphatase 5b (TRACP-5b), number of concomitant phosphate binders, use of sevelamer hydrochloride and laxatives, and Bristol Stool Form Scale (BSFS) scores. Multivariate analysis identified serum TRACP-5b as a significant positive independent predictor and BSFS score as a significant negative independent predictor for requiring higher doses of tenapanor. Elevated TRACP-5b levels and lower BSFS scores were associated with a requirement for higher doses of tenapanor. Incorporating bone turnover and bowel habit assessments into clinical evaluations may support individualized dosing strategies. Large-scale prospective studies in real-world settings are warranted to confirm these findings. Trial registration The original clinical trials were registered at ClinicalTrials.gov under the identifiers NCT04767581 , NCT04766398 , and NCT04766385 .